Evaluasi Kinerja Keuangan Toko Sembako Berdasarkan Solvabilitas dan Likuiditas di Pasar Tradisional Karangjati - Lase, Firman Syukuri; Maria Th, Alleta Dewi (Mahesa Research Center, 2024)
This article aims to evaluate the financial performance of grocery stores in the Karangjati Traditional Market, focusing on solvency and liquidity. This study investigates how these two aspects influence the sustainability of businesses and the financial stability of grocery stores in facing local economic challenges and changes in consumer behavior. Data were collected through in-depth interviews and observations of 11 grocery store owners who have been operating for at least 5 years, using qualitative analysis with a thematic analysis method. The results of the study show that having more than 7 years of experience in managing a store significantly contributes to financial stability, particularly in maintaining solvency and liquidity. Nevertheless, this research has limitations in quantitative analysis, where the addition of solvency and liquidity ratios is necessary to provide a clearer picture of financial health. Furthermore, there is a need to discuss external factors such as inflation and changes in staple food prices that affect financial performance. Therefore, it is recommended to include more in-depth quantitative analysis, discuss relevant external factors, and conduct comparative analysis between stable and less stable stores regarding solvency and liquidity to enrich the understanding of the financial performance of grocery stores.